Nickel silicide nanowire anodes for microbial fuel cells to advance power production and charge transfer efficiency in 3D configurations - Mohammad Hosseini; S. Ahmad Etghani; Mir Razi Mousavi; Mahdieh Joharifar; Mehdi Akbari; Zeinab Sanaee; Shams Mohajerzadeh (Scientific Reports, 2025)
Abstract The growing energy demands of the industrial world have driven advancements in green energy technologies. Microbial fuel cells (MFCs), which harness power from microorganisms, show promise for energy extraction from wastewater and sludge. However, challenges remain in improving power output and sustaining performance under high-charge conditions. Incorporating nanomaterials into 3D structures offers potential solutions, including miniaturized designs. This study introduces nickel silicide nanowires as anode materials for MFCs. Synthesized on nickel foam, these nanowires form a 3D nickel-based structure with semi-metal nanostructures. Tested in a microfluidic MFC system with E. coli, this configuration achieved significant improvements, including a peak power density of 323 mW m-2 and a current density of 2.24 A m-2, representing a 2.5-fold increase in power and a 4-fold boost in current compared to bare nickel foam. Nutrient broth proved the most effective charge transfer medium, surpassing glucose and urea by 3 and 5 times, respectively. These results, supported by EIS and SEM analyses, highlight the role of nanowires in enhancing charge transfer and sustaining high-current performance. The presented 3D nickel-based configuration anode offers advancements in microbial fuel cell technology, providing a foundation for further enhancements and applications in energy harvesting systems.